The Influence of e-Filing Ease of Use, Digital Tax Service Quality, and Data Security System Quality on Individual Taxpayer Compliance Moderated by Risk Preference: A Study on Pizza Hut Network Employees in Indonesia - Wina Kristiani (Interdisciplinary Social Studies, 2025)
This study aims to analyze the effect of ease of e-Filing use, quality of digital tax services, and data security system quality on individual taxpayer compliance, with risk preference as a moderating variable. The research object consists of Pizza Hut employees in Indonesia who are registered individual taxpayers. This quantitative study employs a survey method and Partial Least Squares – Structural Equation Modeling (PLS-SEM) for data analysis. The findings indicate that all three independent variables have a significant positive effect on tax compliance. Risk preference moderates the relationship between ease of e-Filing and service quality with compliance, but does not moderate the effect of data security on compliance. The study contributes theoretically and practically to the development of more inclusive and psychologically informed digital taxation strategies.